EFFECTIVENESS OF MOLYDO OF TEMPERATURE AND HEAT (MTH)-GAME TO IMPROVE STUDENT LEARNING OUTCOMES - Respati Ayu Nikmah Larasati; Mohammad Budiyanto; Enny Susiyawati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This study aimed to produced an educational game media called Molydo of Temperature and Heat (MTH) on the heat and heat transfer material to improve student learning outcomes. The effectiveness of MTH-game was assessed in terms of the improvement of students’learning outcomes. The research method used was Research and Development with the One Group Pretest-Posttest trial design. MTH-game was trialed on 32 grade VII students at SMPN 1 Madiun. Data collection techniques used in this study weretests consisting of a pretest and a posttest. The average of students’ pretest results before learning and using MTH-game was 52.75. For the posttest results, students obtained an average score of 84.50 with a percentage of completeness of 90.60%. In addition,the average N-Gain score for 32 students was 0.69 which was in the medium category. So, MTH-game waseffective in improved student learning outcomes. Keywords: MTH-game, learning outcomes.